AN ANALYSIS OF CODE MIXING IN BAPENO USED BY DEPATI NINIK MAMAK IN HIANG (Al-Qisthu: Jurnal Kajian Ilmu-Ilmu Hukum, 2017)
In communication, a speaker does not only do code mixing in formal context. It can also be found in a certain communication in a special event of a tradition. In fact, the use of code mixing can be found in Bapeno used by Depati Ninik Mamak in Hiang. In Bapeno, Depati Ninik Mamak used code mixing in term of Indonesian language and Hiang dialect or vice verse. This research was conducted concerning the forms and the functions of code mixing in Bapeno by Depati Ninik Mamak in Hiang. This research is a descriptive research. The participants of this reserach were Depati Ninik Mamak in Hiang. This research employed two kinds of data collection techniques; observation and recording. The findings showed that the forms of code mixing in Bapeno by Depati Ninik Mamak in Hiang included in words insertion, phrase insertion, and clause insertion. Then, the function of code mixing in Bapeno by Depati Ninik Mamak in Hiang involved as identity marking and strategy of neutrality. Based on those findings, it was concluded Depati Ninik Mamak did code mixing in Bapeno in Hiang. However, not all of the forms of code mixing used by Depati Ninik Mamak in Bapeno in Hiang. Then, code mixing used by Depati Ninik Mamak in Bapeno did not cover all functions of code mixing.